Efek Penolakan Perubahan Terhadap Niat Menggunakan Aplikasi Apotek K24klik - Yulandari, Ariefah; Satria, Arif Rizki; Setyawan, Didik; Budiadi, Nang Among (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
This study examines the effect of resistance to change in the digitalization of pharmacy services on the intention to use the K24Klik application. The low intention to use the K24Klik application is caused by resistance to change, which is influenced by technological anxiety, security, and dispositional resistance. Data was obtained through questionnaires distributed to people who had never used the K24Klik application with a total sample size of 189—hypothesis testing using SEM (Structural Equation Modeling) with path analysis method. The results of this study show that security and dispositional resistance affect resistance to change, and technology anxiety has no effect on resistance to change, causing low intention to use the K24Klik application.